1987
DOI: 10.1111/j.1600-0528.1987.tb00475.x
|View full text |Cite
|
Sign up to set email alerts
|

Development and application of a prediction model for dental caries

Abstract: The development and validation of a caries prediction model comprising 13 sociodemographic and dental examination variables on Grade 1 and Grade 5 children in the National Preventive Dentistry Demonstration Program are described. The objective was to derive a method of predicting children at high risk to caries early in order that preventive measures might be undertaken. True high risk children were defined in two ways: highest 25% of children based on their 4-yr DMFS increment, and their total DMFS score at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
0
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(43 citation statements)
references
References 4 publications
2
40
0
1
Order By: Relevance
“…A number of authors have published prediction models using generalized linear or logistic regression analysis to support their final explanatory model for caries presence. [6][7][8][9][10][11] Relative risk of disease occurrence or absence over time is often quantified using a surrogate measure such as an odds ratio (OR). 5,[12][13][14][15] On the other hand, a statistical strength of association using sensitivity and specificity measures is often used to report an incremental change in caries over time.…”
Section: Caries Predictionmentioning
confidence: 99%
“…A number of authors have published prediction models using generalized linear or logistic regression analysis to support their final explanatory model for caries presence. [6][7][8][9][10][11] Relative risk of disease occurrence or absence over time is often quantified using a surrogate measure such as an odds ratio (OR). 5,[12][13][14][15] On the other hand, a statistical strength of association using sensitivity and specificity measures is often used to report an incremental change in caries over time.…”
Section: Caries Predictionmentioning
confidence: 99%
“…[13][14][15] However, most of these caries prediction attempts are not noninvasive but minimally invasive and individual level studies. 13,20 The caries prediction model that was generated from our preliminary study is a totally noninvasive population level study as reported by others.…”
Section: Discussionmentioning
confidence: 99%
“…13,20 The caries prediction model that was generated from our preliminary study is a totally noninvasive population level study as reported by others. 14,15 Further, several recent reviews 13,21 have highlighted the importance of having minimally invasive dentistry caries management strategies that should be incorporated to estimate caries activity at each visit. These reviews 13,21,22 have also highlighted the current lack of such methods validated for reliable and precise estimation of caries activity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations